PENGELOLAAN PENJAMINAN MUTU DI SMP NEGERI 2 TELUK KERAMAT - Bayu, Bayu; Radiana, Usman; Wahyudi, Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe and know: (1) Quality assurance planning in Teluk Keramat Middle School 2. (2) Implementation of quality assurance in the Keramat Teluk 2 Public Middle School. (3) Quality assurance evaluation in Teluk Keramat Middle School 2. (4) Supporting and inhibiting factors for the implementation of quality assurance in Teluk Keramat Middle School 2. The research method used is a case study approach with a form of qualitative research. The data sources of this study were 3 people consisting of 2 men and 1 women, namely the principal of Alwan, M. Pd (52), wk. curriculum Sri Hartati, S.Pd (54), and chairman of the quality assurance team M.Amin, S.Pd (54) and the data are through data collection techniques using interview, observation, and documentation techniques. While data analysis techniques are used through the stages of data reduction, data presentation, and conclusion drawing.The results of the study can be concluded that: (1) Quality assurance planning in Teluk Keramat Middle School 2 has followed the guidelines issued by the Directorate General of Secondary Education of the Ministry of Education and Culture. (2) In the implementation of this quality assurance the principal involves all parties in the school, including public relations vice principal, vice principal of curriculum, vice facility of infrastructure, vice principal of student affairs, teacher, administration, and students. (3) Evaluation of quality assurance in Teluk Keramat Middle School 2 is carried out through formal and informal conversations to discuss the results of the assessment of quality assurance activities. (4) Supporting factors: First, the teacher is much proactive, compact and solid. Second, the condition of the school is quite safe. Third, the school committee always supports and trusts. Fourth, supervisors of supervisors are always present if asked for assistance such as being a resource person at the MGMP event. While inhibiting factors such as funding because it only comes from BOS funds and limited time to be able to complete all the work that is in school, human resources are limited because only a few human resources have the desire to improve the quality of schools.Â Keywords: Management, Quality Assurance